Membrane Stabilizing and Cytotoxic Activities of Different Kupchan Partitionates of Oroxylum indicum (L.) Vent. Leaf and Bark Extracts - Aktar, Fahima; Kuddus, Md Ruhul; Kabir, Shaila; Rashid, Mohammad A; Chakma, Ketoki (Dhaka University Journal of Pharmaceutical Sciences, 2014)
Abstract not available Dhaka Univ. J. Pharm. Sci. 12(2): 181-183, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17625